Polymer solid electrolyte with long service life and wide electrochemical window and preparation method thereof
By introducing the biquinolinium structure into the polymer solid electrolyte, the problems of insufficient stability and narrow electrochemical window of the solid electrolyte at high voltage are solved, and the electrolyte's high electrochemical activity, wide electrochemical window and long life characteristics are achieved. .
Patent Information
- Application Number
- CN202411380127.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing solid electrolytes have insufficient stability at high voltages, a narrow electrochemical window, and are prone to performance decay during long-term circulation.
Through the innovative polymer design and preparation process, a 4,4'-linked pyrinol-linolin intermediate product was generated by the heating reactions of pyrine and metal sodium, and a series of substituted reactions and anion exchange reactions were introduced. In the polymell hydroxeroxane, the solid electrolyte of the modified polymer is formed.
It significantly improves the electrochemical activity and ionic conductivity of the electrolyte, expands the electrochemical window, enhances thermal stability and mechanical strength, and ensures the stable performance of the battery under high voltage and long cycle conditions.
Smart Images

Figure BDA0005069694880000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid electrolytes, and in particular to a long-life wide electrochemical window polymer solid electrolyte and a preparation method thereof. Background Art
[0002] As one of the core components of lithium-ion batteries, solid electrolytes play a vital role in improving the energy density, safety and cycle stability of batteries. Although traditional liquid electrolytes have high ionic conductivity, they have problems such as easy leakage, flammability and poor chemical stability, which limit the further improvement of battery performance and the expansion of application scope. In order to overcome these defects, solid electrolytes have attracted widespread attention due to their non-flammability, no leakage and good thermal stability.
[0003] Solid electrolytes are mainly divided into two categories: inorganic and organic. Inorganic solid electrolytes such as oxides and sulfides usually have high ionic conductivity, but their interfacial compatibility with electrode materials is poor, resulting in increased interfacial resistance and affecting the overall performance of the battery. On the other hand, organic solid electrolytes, especially those based on polysiloxane, show great potential due to their good mechanical properties and flexibility. However, their narrow electrochemical window limits their application in high-voltage battery systems.
[0004] Currently, researchers are committed to developing new solid electrolyte materials to achieve high ionic conductivity, wide electrochemical window and excellent interface compatibility. These materials need to have good electrochemical performance at room temperature while remaining stable at high voltage to meet the needs of next-generation high-energy density batteries. Although some progress has been made, the development of solid electrolytes with long life and wide electrochemical window remains a challenge and requires further research and innovation. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a method for preparing a long-life wide electrochemical window polymer solid electrolyte to solve the problems of insufficient stability of existing solid electrolytes under high voltage, narrow electrochemical window, and easy performance degradation during long-term cyclic use. Specifically, the electrolyte materials in the prior art often face challenges such as easy decomposition when operating at high voltage, large changes in conductivity with temperature, and insufficient mechanical properties. These problems limit the performance and application range of solid-state batteries. The present invention aims to overcome these limitations through innovative polymer design and preparation processes, and provide a polymer solid electrolyte with better comprehensive performance to meet the needs of high energy density and high safety solid-state batteries.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A method for preparing a long-life wide electrochemical window polymer solid electrolyte, the preparation method comprising the following steps:
[0008] S1: heating a quinoline compound and metallic sodium to react for a certain period of time, and obtaining a 4,4'-biquinoline intermediate product (as shown in structural formula I) after separation;
[0009] In the formula, R1, R2, R3, and R4 are independently selected from hydrogen or methyl;
[0010] S2: first subjecting the 4,4'-biquinoline intermediate obtained in step S1 to a mono-substitution reaction with a brominated alkane; then adding vinyl bromide to carry out a di-substitution reaction, then adding divinyl ether to carry out an addition reaction, and finally adding an aqueous solution containing fluorine anions to carry out anion exchange reaction to obtain a terminal olefin biquinolinium compound (as shown in structural formula II);
[0011] In the formula, R5 is an alkane with 2 to 5 carbon atoms; n is 1, 2 or 3; X - is tetrafluoroborate, trifluoromethanesulfonate or hexafluorophosphate;
[0012] S3: performing a disubstituted reaction of the 4,4'-biquinoline intermediate obtained in step S1 with a brominated olefin; then adding an aqueous solution containing fluorine anions to perform an anion exchange reaction to obtain a diolefin biquinolinium compound (as shown in structural formula III);
[0013] In the formula, R6 and R7 are independently selected from olefins having 3 to 6 carbon atoms; X - is tetrafluoroborate, trifluoromethanesulfonate or hexafluorophosphate;
[0014] S4: dissolving a certain amount of polymethyl hydrogen siloxane in a solvent by heating and stirring, adding a mixture of the terminal olefin biquinolinium compound obtained in step S2, a catalyst and a solvent, and heating and reacting under inert atmosphere protection to obtain modified polymethyl hydrogen siloxane;
[0015] S5: stirring and dissolving the modified polymethylhydrogensiloxane obtained in step S4 in a solvent, then adding the diolefin biquinolinium compound, catalyst and lithium bis(trifluoromethylsulfonyl)imide obtained in step S3, stirring and mixing evenly at room temperature, placing in a vacuum oven, heating and cross-linking and curing to obtain the polymer solid electrolyte.
[0016] The present invention synthesizes 4,4'-biquinolinium grafted modified polymethylhydrogensiloxane through steps S1, S2 and S4. Through the introduction of biquinolinium, it not only realizes intrinsic conductive properties and significantly improves the electrochemical activity and ionic conductivity of the electrolyte, but also the conjugated structure of biquinolinium further enhances the electrochemical window and thermal stability of the electrolyte. In addition, the 4,4'-biquinolinium grafted modified polymethylhydrogensiloxane also enhances the mechanical strength of the electrolyte, so that it maintains structural stability during the long-term cycle of the battery. At the same time, the introduced ether functional group further increases the flexibility of the solid electrolyte and promotes ion migration, thereby improving the ionic conductivity of the electrolyte, especially the electrochemical performance in a wide temperature range.
[0017] The present invention also synthesizes a 4,4'-biquinolinium compound having a diolefin structure through steps S1 and S3. In step S5, it is used as an efficient cross-linking agent to cross-link with the remaining silicon-hydrogen bonds in polymethylhydrogensiloxane under the action of a catalyst to obtain a polymer solid electrolyte with a three-dimensional cross-linked network structure having high electrochemical stability and excellent mechanical properties. In this process, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) is used as a lithium salt, which not only improves the ionic conductivity of the electrolyte due to its good ionic conductivity, but also further enhances the performance of the electrolyte due to its chemical stability and compatibility with electrode materials. The polymer solid electrolyte of the present invention not only has a wider electrochemical window, ensuring chemical stability under high voltage operation, but also the electrolyte membrane formed by in-situ polymerization curing exhibits excellent chemical and electrochemical stability, as well as good interface compatibility with electrode materials. These characteristics provide an important material basis for the development of high energy density and high safety solid-state batteries, and also provide strong support for the long cycle life and wide operating temperature range of the battery.
[0018] As a preferred technical solution, in step S4, the heating reaction is first reacted at a temperature of 45-55° C. for 2-4 hours, and then the temperature is raised to 80-90° C. for a further 2-4 hours.
[0019] As a preferred technical solution, the quinoline compound is at least one of quinoline, 3-methylquinoline, 5-methylquinoline, 6-methylquinoline, 7-methylquinoline, 8-methylquinoline, 2,3-dimethylquinoline, 2,6-dimethylquinoline, 2,7-dimethylquinoline, 2,8-dimethylquinoline, 5,8-dimethylquinoline, 6,7-dimethylquinoline, 6,8-dimethylquinoline, 2,6,7-trimethylquinoline, 2,6,8-trimethylquinoline, 2,5,7-trimethylquinoline, 2,7,8-trimethylquinoline and 2,5,8-trimethylquinoline.
[0020] As a preferred technical solution, the brominated alkane is at least one of ethyl bromide, propyl bromide, butyl bromide and pentane bromide.
[0021] As a preferred technical solution, the divinyl ether is at least one of ethylene glycol divinyl ether, diethylene glycol divinyl ether and triethylene glycol divinyl ether.
[0022] As a preferred technical solution, the fluorine-containing anion is at least one of tetrafluoroborate, trifluoromethanesulfonate, and hexafluorophosphate.
[0023] As a preferred technical solution, the brominated olefin is at least one of 3-bromopropylene, 3-bromo-2-methylpropylene, 3-bromo-1-butene, 4-bromo-2-methyl-1-butene, 5-bromo-1-pentene, 5-bromo-1-hexene, and 6-bromo-1-hexene.
[0024] As a preferred technical solution, the catalyst is at least one of chloroplatinic acid, palladium acetate, and nickel acetate.
[0025] As a preferred technical solution, the mass ratio of the terminal olefin biquinolinium compound to polymethyl hydrogen siloxane is 10 to 15:1.
[0026] As a preferred technical solution, the mass ratio of the diolefin biquinolinium compound to the modified polymethyl hydrogen siloxane is 2 to 3:1.
[0027] Another aspect of the present invention is to provide a long-life wide electrochemical window polymer solid electrolyte, wherein the polymer solid electrolyte is prepared by the above-mentioned preparation method of the long-life wide electrochemical window polymer solid electrolyte.
[0028] Beneficial effects of the present invention:
[0029] The long-life wide electrochemical window polymer solid electrolyte prepared by the present invention not only realizes stable operation under a wide electrochemical window, ensures the safety and reliability of the battery under high voltage conditions, but also significantly improves the long-life characteristics of the electrolyte through optimized chemical structure and cross-linked network design, allowing the battery to undergo more charge and discharge cycles without performance decay. In addition, the electrolyte of the present invention also has good mechanical properties and thermal stability, further enhancing the environmental adaptability and durability of the battery. In addition, the preparation method of the present invention is simple to operate, easy to scale production, conducive to reducing costs, and promoting the commercialization process of solid-state battery technology. DETAILED DESCRIPTION
[0030] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0031] Example 1
[0032] The method for preparing the long-life wide electrochemical window polymer solid electrolyte of this embodiment comprises the following steps:
[0033] S1: Add 0.2 mol quinoline and 0.05 mol sodium metal into a reaction bottle, heat to 120°C for 24 hours, cool to room temperature and pour into ice cubes to complete the reaction of excess sodium metal; add anhydrous sodium sulfate to the obtained oil after oil-water separation, let stand overnight, and then remove excess quinoline by rotary evaporation under reduced pressure; the product obtained after rotary evaporation is recrystallized in ethanol solution to obtain 4,4'-biquinoline intermediate.
[0034] S2: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.04 mol of ethyl bromide was added to carry out a monosubstitution reaction for 5 h; then 0.042 mol of vinyl bromide was added to carry out a disubstitution reaction for 5 h, followed by adding 0.042 mol of triethylene glycol divinyl ether and an appropriate amount of initiator, heating to 60° C. for an addition reaction for 1 h, and finally adding a 30% mass concentration of sodium tetrafluoroborate aqueous solution for an anion exchange reaction, and obtaining a terminal olefin biquinolinium compound after separation.
[0035] S3: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.085 mol of 3-bromopropylene was added to carry out a disubstitution reaction for 6 hours; then a 30% sodium tetrafluoroborate aqueous solution was added to carry out an anion exchange reaction, and a diolefin biquinolinium compound was obtained after separation.
[0036] S4: 55 g of polymethyl hydrogen siloxane (average molecular weight of 2100) was dissolved in 100 mL of xylene solvent by heating and stirring, and a mixture prepared by 5.8 g of the terminal olefin biquinolinium compound obtained in step S2, 0.8 g of catalyst chloroplatinic acid and 100 mL of xylene solvent was added, and a heating reaction was carried out under nitrogen atmosphere protection. The heating reaction was first reacted at a temperature of 45° C. for 3 hours, and then the temperature was raised to 80° C. and the reaction was continued for 4 hours. After separation, modified polymethyl hydrogen siloxane was obtained.
[0037] S5: 30 g of the modified polymethylhydrogensiloxane obtained in step S4 is stirred and dissolved in 60 mL of solvent xylene, and then 10 g of the diolefin biquinolinium compound obtained in step S3, 0.5 g of catalyst chloroplatinic acid and 4.5 g of lithium bis(trifluoromethylsulfonyl)imide are added, and the mixture is stirred and mixed evenly at room temperature. The mixture is placed in a vacuum oven and heated to 105° C. for cross-linking and curing reaction for 24 hours to obtain the polymer solid electrolyte.
[0038] Example 2
[0039] The method for preparing the long-life wide electrochemical window polymer solid electrolyte of this embodiment comprises the following steps:
[0040] S1: Add 0.2 mol 6-methylquinoline and 0.05 mol sodium metal into a reaction bottle, heat to 120°C for 24 hours, cool to room temperature and pour into ice cubes to complete the reaction of excess sodium metal; add anhydrous sodium sulfate to the obtained oil after oil-water separation, let stand overnight, and then remove excess quinoline by rotary evaporation under reduced pressure; the product obtained after rotary evaporation is recrystallized in ethanol solution to obtain 4,4'-biquinoline intermediate.
[0041] S2: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.04 mol of bromopropane was added to carry out a monosubstitution reaction for 5 h; then 0.042 mol of vinyl bromide was added to carry out a disubstitution reaction for 5 h, followed by adding 0.042 mol of diethylene glycol divinyl ether and an appropriate amount of initiator, and heated to 60° C. for an addition reaction for 1 h, and finally a 30% mass concentration of sodium trifluoromethanesulfonate aqueous solution was added to carry out anion exchange reaction, and a terminal olefin biquinolinium compound was obtained after separation.
[0042] S3: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.085 mol of 3-bromo-2-methylpropylene was added to carry out a disubstitution reaction for 6 hours; then a 30% sodium trifluoromethanesulfonate aqueous solution was added to carry out anion exchange reaction, and a diolefin biquinolinium compound was obtained after separation.
[0043] S4: 55 g of polymethyl hydrogen siloxane (average molecular weight of 2100) was dissolved in 100 mL of solvent xylene by heating and stirring, and a mixture prepared by 6.2 g of terminal olefin biquinolinium compound obtained in step S2, 0.8 g of catalyst chloroplatinic acid and 100 mL of solvent xylene was added, and a heating reaction was carried out under nitrogen atmosphere protection. The heating reaction was first reacted at a temperature of 55° C. for 2 h, and then the temperature was raised to 90° C. and the reaction was continued for 2 h. After separation, modified polymethyl hydrogen siloxane was obtained.
[0044] S5: 30 g of the modified polymethylhydrogensiloxane obtained in step S4 is stirred and dissolved in 60 mL of solvent xylene, and then 11 g of the diolefin biquinolinium compound obtained in step S3, 0.5 g of catalyst chloroplatinic acid and 4.5 g of lithium bis(trifluoromethylsulfonyl)imide are added, and the mixture is stirred and mixed evenly at room temperature. The mixture is placed in a vacuum oven and heated to 105° C. for cross-linking and curing reaction for 24 hours to obtain the polymer solid electrolyte.
[0045] Example 3
[0046] The method for preparing the long-life wide electrochemical window polymer solid electrolyte of this embodiment comprises the following steps:
[0047] S1: Add 0.2 mol 7-methylquinoline and 0.05 mol sodium metal into a reaction bottle, heat to 120°C for 24 hours, cool to room temperature and pour into ice cubes to complete the reaction of excess sodium metal; add anhydrous sodium sulfate to the obtained oil after oil-water separation, let stand overnight, and then remove excess quinoline by rotary evaporation under reduced pressure; the product obtained after rotary evaporation is recrystallized in ethanol solution to obtain 4,4'-biquinoline intermediate.
[0048] S2: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.04 mol of bromobutyl was added to carry out a monosubstitution reaction for 5 h; then 0.042 mol of vinyl bromide was added to carry out a disubstitution reaction for 5 h, followed by adding 0.042 mol of ethylene glycol divinyl ether and an appropriate amount of initiator, and heated to 60° C. for an addition reaction for 1 h, and finally a 30% mass concentration of sodium hexafluorophosphate aqueous solution was added to carry out anion exchange reaction, and a terminal olefin biquinolinium compound was obtained after separation.
[0049] S3: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 is dissolved in 50 mL of acetonitrile solution, and 0.085 mol of 4-bromo-2-methyl-1-butene is added to carry out a disubstitution reaction for 6 hours; then a sodium hexafluorophosphate aqueous solution with a mass concentration of 30% is added to carry out an anion exchange reaction, and a diolefin biquinolinium compound is obtained after separation.
[0050] S4: 55 g of polymethyl hydrogen siloxane (average molecular weight of 2100) was dissolved in 100 mL of xylene solvent by heating and stirring, and a mixture prepared by 6.5 g of the terminal olefin biquinolinium compound obtained in step S2, 0.8 g of catalyst chloroplatinic acid and 100 mL of xylene solvent was added, and a heating reaction was carried out under nitrogen atmosphere protection. The heating reaction was first reacted at a temperature of 50° C. for 4 hours, and then the temperature was raised to 80° C. and the reaction was continued for 4 hours. After separation, modified polymethyl hydrogen siloxane was obtained.
[0051] S5: 30 g of the modified polymethylhydrogensiloxane obtained in step S4 is stirred and dissolved in 60 mL of solvent xylene, and then 12 g of the diolefin biquinolinium compound obtained in step S3, 0.5 g of catalyst chloroplatinic acid and 4.5 g of lithium bis(trifluoromethylsulfonyl)imide are added, and the mixture is stirred and mixed evenly at room temperature. The mixture is placed in a vacuum oven and heated to 105° C. for cross-linking and curing reaction for 24 hours to obtain the polymer solid electrolyte.
[0052] Example 4
[0053] The method for preparing the long-life wide electrochemical window polymer solid electrolyte of this embodiment comprises the following steps:
[0054] S1: Add 0.2 mol 6,8-dimethylquinoline and 0.05 mol sodium metal into a reaction bottle, heat to 120°C for 24 hours, cool to room temperature and pour into ice cubes to complete the reaction of excess sodium metal; add anhydrous sodium sulfate to the obtained oil after oil-water separation, let stand overnight, and then remove excess quinoline by rotary evaporation under reduced pressure; the product obtained after rotary evaporation is recrystallized in ethanol solution to obtain 4,4'-biquinoline intermediate.
[0055] S2: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.04 mol of bromopentane was added to carry out a monosubstitution reaction for 5 h; then 0.042 mol of vinyl bromide was added to carry out a disubstitution reaction for 5 h, followed by adding 0.042 mol of diethylene glycol divinyl ether and an appropriate amount of initiator, heating to 60° C. for an addition reaction for 1 h, and finally adding a 30% mass concentration of sodium tetrafluoroborate aqueous solution for an anion exchange reaction, and obtaining a terminal olefin biquinolinium compound after separation.
[0056] S3: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.085 mol of 5-bromo-1-pentene was added to carry out a disubstitution reaction for 6 hours; then a 30% mass concentration of sodium tetrafluoroborate aqueous solution was added to carry out anion exchange reaction, and a diolefin biquinolinium compound was obtained after separation.
[0057] S4: 55 g of polymethyl hydrogen siloxane (average molecular weight of 2100) was dissolved in 100 mL of xylene solvent by heating and stirring, and a mixture prepared by 6.8 g of the terminal olefin biquinolinium compound obtained in step S2, 0.8 g of catalyst chloroplatinic acid and 100 mL of xylene solvent was added, and a heating reaction was carried out under nitrogen atmosphere protection. The heating reaction was first reacted at a temperature of 50° C. for 3 hours, and then the temperature was raised to 80° C. and the reaction was continued for 4 hours. After separation, modified polymethyl hydrogen siloxane was obtained.
[0058] S5: 30 g of the modified polymethylhydrogensiloxane obtained in step S4 is stirred and dissolved in 60 mL of solvent xylene, and then 13 g of the diolefin biquinolinium compound obtained in step S3, 0.5 g of catalyst chloroplatinic acid and 4.5 g of lithium bis(trifluoromethylsulfonyl)imide are added, and the mixture is stirred and mixed evenly at room temperature. The mixture is placed in a vacuum oven and heated to 105° C. for cross-linking and curing reaction for 24 hours to obtain the polymer solid electrolyte.
[0059] Example 5
[0060] The method for preparing the long-life wide electrochemical window polymer solid electrolyte of this embodiment comprises the following steps:
[0061] S1: Add 0.2 mol 2,6,7-trimethylquinoline and 0.05 mol sodium metal into a reaction bottle, heat to 120°C for 24 hours, cool to room temperature and pour into ice cubes to complete the reaction of excess sodium metal; add anhydrous sodium sulfate to the obtained oil after oil-water separation, let stand overnight, and then remove excess quinoline by rotary evaporation under reduced pressure; the product obtained after rotary evaporation is recrystallized in ethanol solution to obtain 4,4'-biquinoline intermediate.
[0062] S2: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 was dissolved in 50 mL of acetonitrile solution, and 0.04 mol of ethyl bromide was added to carry out a monosubstitution reaction for 5 h; then 0.042 mol of vinyl bromide was added to carry out a disubstitution reaction for 5 h, followed by adding 0.042 mol of ethylene glycol divinyl ether and an appropriate amount of initiator, heating to 60° C. for an addition reaction for 1 h, and finally adding a 30% mass concentration of sodium tetrafluoroborate aqueous solution for an anion exchange reaction, and obtaining a terminal olefin biquinolinium compound after separation.
[0063] S3: 0.04 mol of the 4,4'-biquinoline intermediate obtained in step S1 is dissolved in 50 mL of acetonitrile solution, and 0.085 mol of 6-bromo-1-hexene is added to carry out a disubstitution reaction for 6 hours; then a 30% mass concentration of sodium tetrafluoroborate aqueous solution is added to carry out anion exchange reaction, and a diolefin biquinolinium compound is obtained after separation.
[0064] S4: 55 g of polymethyl hydrogen siloxane (average molecular weight of 2100) was dissolved in 100 mL of xylene solvent by heating and stirring, and a mixture prepared by 7.2 g of the terminal olefin biquinolinium compound obtained in step S2, 0.8 g of catalyst chloroplatinic acid and 100 mL of xylene solvent was added, and a heating reaction was carried out under nitrogen atmosphere protection. The heating reaction was first reacted at a temperature of 50° C. for 3 hours, and then the temperature was raised to 90° C. and the reaction was continued for 2 hours. After separation, modified polymethyl hydrogen siloxane was obtained.
[0065] S5: 30 g of the modified polymethylhydrogensiloxane obtained in step S4 is stirred and dissolved in 60 mL of solvent xylene, and then 14 g of the diolefin biquinolinium compound obtained in step S3, 0.5 g of catalyst chloroplatinic acid and 4.5 g of lithium bis(trifluoromethylsulfonyl)imide are added, and the mixture is stirred and mixed evenly at room temperature. The mixture is placed in a vacuum oven and heated to 105° C. for cross-linking and curing reaction for 24 hours to obtain the polymer solid electrolyte.
[0066] Comparative Example 1
[0067] The raw material composition and preparation steps of the polymer solid electrolyte preparation method of this comparative example are basically the same as those of Example 1, except that, in the polymer solid electrolyte preparation method of this comparative example, triethylene glycol divinyl ether is not added in step S2 for addition reaction.
[0068] Comparative Example 2
[0069] The raw material composition and preparation steps of the polymer solid electrolyte preparation method of this comparative example are basically the same as those of Example 1, except that in the polymer solid electrolyte preparation method of this comparative example, 3-bromopropylene is not added in step S3 for di-substitution reaction.
[0070] The polymer solid electrolytes prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to performance tests, and the performance results are shown in Table 1:
[0071] Among them, the mechanical strength performance test method is: the example sample is cut into long strips with a length of 120 mm and a width of 15 mm. The mechanical strength of the polymer solid electrolyte is evaluated by a tensile test on a universal material testing machine, with tensile strength and elongation at break as evaluation indicators.
[0072] Ionic conductivity test method: Electrochemical impedance spectroscopy (EIS) was used to measure ionic conductivity.
[0073] Electrochemical stability window test method: The electrochemical stability window of the electrolyte is determined by cyclic voltammetry (CV), which measures the maximum voltage range that the electrolyte can withstand without decomposition.
[0074] Interface compatibility test method: The interface stability between the solid electrolyte and the electrode material is evaluated by battery cycle testing to evaluate the long-life performance of the solid electrolyte. Specifically, the solid electrolyte sample of the embodiment is first packaged into a solid-state battery with the positive electrode material lithium iron phosphate and the negative electrode material lithium titanate, and then the charge and discharge rate is set to C / 10 (the battery completes a full charge process within 10 hours). The voltage range is set at 1.0 to 5.0V, and the test is continued for 100 cycles. After 100 charge and discharge cycles, the capacity retention rate of the battery is used as an evaluation index. Table 1
[0075] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. A method for preparing a long-life wide electrochemical window polymer solid electrolyte, characterized in that: The preparation method comprises the following steps: S1: heating the quinoline compound and metallic sodium for a certain period of time to obtain a 4,4'-biquinoline intermediate after separation; S2: first subjecting the 4,4'-biquinoline intermediate obtained in step S1 to a mono-substitution reaction with a brominated alkane; then adding vinyl bromide to carry out a di-substitution reaction, then adding divinyl ether to carry out an addition reaction, and finally adding an aqueous solution containing fluorine anions to carry out anion exchange reaction to obtain a terminal olefin biquinolinium compound; S3: performing a disubstituted reaction of the 4,4'-biquinoline intermediate obtained in step S1 with a brominated olefin; then adding an aqueous solution containing fluorine anions to perform an anion exchange reaction to obtain a diolefin biquinolinium compound; S4: dissolving a certain amount of polymethyl hydrogen siloxane in a solvent by heating and stirring, adding a mixture of the terminal olefin biquinolinium compound obtained in step S2, a catalyst and a solvent, and heating and reacting under inert atmosphere protection to obtain modified polymethyl hydrogen siloxane; S5: stirring and dissolving the modified polymethylhydrogensiloxane obtained in step S4 in a solvent, then adding the diolefin biquinolinium compound, catalyst and lithium bis(trifluoromethylsulfonyl)imide obtained in step S3, stirring and mixing evenly at room temperature, placing in a vacuum oven, heating and cross-linking and curing to obtain the polymer solid electrolyte.
2. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The quinoline compound is at least one of quinoline, 3-methylquinoline, 5-methylquinoline, 6-methylquinoline, 7-methylquinoline, 8-methylquinoline, 2,3-dimethylquinoline, 2,6-dimethylquinoline, 2,7-dimethylquinoline, 2,8-dimethylquinoline, 5,8-dimethylquinoline, 6,7-dimethylquinoline, 6,8-dimethylquinoline, 2,6,7-trimethylquinoline, 2,6,8-trimethylquinoline, 2,5,7-trimethylquinoline, 2,7,8-trimethylquinoline and 2,5,8-trimethylquinoline.
3. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The brominated alkane is at least one of ethyl bromide, propyl bromide, butyl bromide and pentane bromide.
4. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The divinyl ether is at least one of ethylene glycol divinyl ether, diethylene glycol divinyl ether and triethylene glycol divinyl ether.
5. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The fluorine-containing anion is at least one of tetrafluoroborate, trifluoromethanesulfonate and hexafluorophosphate.
6. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The brominated olefin is at least one of 3-bromopropylene, 3-bromo-2-methylpropylene, 3-bromo-1-butene, 4-bromo-2-methyl-1-butene, 5-bromo-1-pentene, 5-bromo-1-hexene and 6-bromo-1-hexene.
7. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The catalyst is at least one of chloroplatinic acid, palladium acetate and nickel acetate.
8. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of the terminal olefin biquinolinium compound to polymethyl hydrogen siloxane is 10-15:
1.
9. The method for preparing the long-life wide electrochemical window polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of the diolefin biquinolinium compound to the modified polymethyl hydrogen siloxane is 2 to 3:
1.
10. A long-life wide electrochemical window polymer solid electrolyte, characterized in that: The polymer solid electrolyte is prepared by the method for preparing a long-life and wide electrochemical window polymer solid electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Comb polysilicone and solid electrolyte, preparation method and application thereof
CN103421190A
Zwitter-ion-containing all-solid-state polymer electrolyte membrane, and preparation method and use thereof
CN106549187A
Silicotungstic acid-inner salt terminated polystyrene hybrid electrolyte material and preparation method thereof
CN113036217A
Self-supporting polymer solid electrolyte and preparation method thereof
CN118667065A
Novel wide electrochemical window polymer solid electrolyte and preparation method thereof
CN119340464A